Non-binary LDPC Decoder Design over Rayleigh Channel for FPGA Implementation - Zhongxun Wang; Juan Hui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexLow Density Parity Check Code（LDPC） is a kind of linear block codes based on sparse check matrix. As a kind of channel coding, whose error performance approach Shannon limits, it has better error correction capability, more flexible structure and lower decoding complexity. Currently most of the LDPC code researches are on the premise of the AWGN channel and BSC channel, which mainly in the range of the binary LDPC codes. According to the above problem, this paper analyzes the various decoding performance of non-binary LDPC codes in Rayleigh channel, and realizes a non-binary LDPC decoder in Rayleigh channel through the FPGA design. The paper begins with an overall discussion of issues surrounding the use of non-binary LDPC codes. And then the bit-error-rate (BER) performances of different non-binary LDPC codes decoding algorithm are compared on the independent Rayleigh fading channel. Finally, this decoder design is implemented based on 5CSEMA5F31C6 FPGA (devised by Altera Company) to illustrate the concepts discussed in the paper.